Penataan Desa Terdampak Lumpur di Kabupaten Sidoarjo - Dyah Retno Karlina; Rizari; Faria Ruhana (Syntax Idea)
This study discusses collaborative governance in managing mud-affected villages in Sidoarjo Regency. The Sidoarjo mudflow has occurred since 2004 and until now there has been no final decision regarding the arrangement of the affected villages in the three sub-districts namely Porong, Jabon and Tanggulangin. Meanwhile, the community and villages affected by the mud must immediately receive follow-up so that they can carry out their functions properly. This research serves to analyze how the process of village arrangement, supporting factors and inhibiting factors as well as efforts to overcome them. Referring to the collaborative governance model according to Ansel and Gash with a descriptive qualitative research method. The author uses data collection techniques through observation, interviews, and documentation. The results of the study show that collaborative governance has been carried out in the process of structuring villages affected by the Sidoarjo mudflow quite well covering the initial conditions related to inadequate human resources in terms of quantity and supporting financial resources, institutional design related to institutions that are already good, basic rules that already exist , and transparency that has been carried out, facilitative leadership by stakeholders, and collaborative processes related to face to face dialogue, building trust and understanding between collaboration participants, sharing understanding and mission as well as intermediate outcomes in the form of review papers and draft regional regulations. However, there are still inhibiting factors, namely the initial condition of inadequate human resources in quantity, the process of formulating village arrangements that took too long and the community's understanding that could not be uniformed resulted in obstacles in the process of structuring villages affected by the Sidoarjo mudflow.